Type 1 interferon signature in peripheral blood mononuclear cells and monocytes of idiopathic inflammatory myopathy patients with different myositis-specific autoantibodies - Li, Mengdi; Zhang, Yusheng; Zhang, Wenzhe; Sun, Jinlei; Liu, Rui; Pan, Zhou; Zhang, Panpan; Liu, Shengyun (Frontiers in Immunology, 2023)
Background: Myositis-specific autoantibodies (MSAs) are clinically used to diagnose and define idiopathic inflammatory myopathies (IIM) subsets. However, the underlying pathogenic mechanisms of patients with different MSAs remain unclear. Methods: A total of 158 Chinese patients with IIM and 43 gender- and age- matched healthy controls (HCs) were enrolled. Transcriptome sequencing (RNA-Seq) was performed with peripheral blood mononuclear cells (PBMCs), followed by the identification of differentially expressed genes (DEGs) and analysis of GSEA, immune cell infiltration, and WGCNA. Monocyte subsets and related cytokines/chemokines were quantified. Expressions of interferon (IFN)-related genes were validated using qRT-PCR and Western blot in both PBMCs and monocytes. We also performed correlation analysis and ROC analysis to explore the potential clinical significance of the IFN-related genes. Results: There were 1364 genes altered in patients with IIM, including 952 upregulated and 412 downregulated genes. The type I interferon (IFN-I) pathway was remarkably activated in patients with IIM. Compared with patients of other MSAs, IFN-I signatures were significantly activated in patients with anti-MDA5 antibodies. 1288 hub genes associated with IIM onset were identified using WGCNA, including 29 key DEGs associated with IFN signaling. Patients had more CD14brightCD16- classical, CD14brightCD16+ intermediate and fewer CD14dimCD16+ non-classical monocyte subsets. Plasma cytokines like IL-6, TNF and chemokines including CCL3, MCPs increased. Validation of IFN-I-related gene expressions was consistent with the findings from RNA-Seq. IFN-related genes were correlated with laboratory parameters and helpful for IIM diagnosis. Conclusion: Gene expressions were remarkably altered in PBMCs of IIM patients. Anti-MDA5+ IIM patients had a more pronounced activated IFN signature than others. Monocytes exhibited a proinflammatory feature and contributed to the IFN signature of IIM patients.